Seasonal changes in physiological characteristics and yield in newly opened trees of Hevea brasiliensis in North Konkan - Chandrasekhar T R; Jana M K; Sethuraj M R; Thomas J; Vijayakumar K R (Indian Journal of Natural Rubber Research, 1990)
Seasonal changes in physiological characteristics and yield were studied in Hevea brasiliensis in the Noth Konkan region. This is a non-traditional rubber growing area where the crop experiences severe drought in summer months. The study was carried out in newly opened trees of clones GT 1 and RRIM 600. The per tap dry rubber yield in summer months was extremely low and not economical. The estimated first year yield ha-1 for the remaining period was 493 kg for GT 1 and 549 kg for RRIM 600. The extreme soil and atmospheric moisture deficits resulted in very low plant moisture status and high plugging indices. Stomatal conductance and transpiration rates were also severely inhibited throughout the day. Partial defoliation and leaf margin drying were observed during this period. In general, RRIM 600 maintained relatively higher yield and plant moisture status.
Keywords: Drought tolerance; Drought tolerance; Hevea brasiliensis; Hevea brasiliensis; Konkan region; Konkan region; Water relations; Water relations; Yield components; Yield components